Prevalence and Self-Perceived Experiences With the Use of Hormonal Contraceptives Among Competitive Female Cross-Country Skiers and Biathletes in Norway: The FENDURA Project - Engseth, Tina P.; Andersson, Erik P.; Solli, Guro S.; Morseth, Bente; Thomassen, Tor Oskar; Noordhof, Dionne A.; Sandbakk, Øyvind; Welde, Boye (Frontiers in Sports and Active Living, 2022)
Purpose: To investigate the prevalence of hormonal contraceptive (HC) use by female endurance athletes on different performance levels, their reasons for HC use, and to compare negative symptoms related to the HC-/menstrual cycle in HC users and non-HC users. Additionally, characterized the self-perceived influence of HC use on training and performance. Methods: A total of 113 Norwegian competitive cross-country (XC) skiers and biathletes completed an online questionnaire including both closed and open-ended questions. The questions were designed to assess the type of HC, reasons for use, self-reported negative symptoms related to HC-/menstrual cycle, as well as athletes’ experiences regarding how HC use affects training and performance. Results: In total, 68% of all the athletes used HC, with 64% and 36% of them using a progestin-only and combined type HC, respectively. Non-contraceptive reasons for HC use were reported by 51% of the progestin-only HC users vs. 75% of the combined HC users (P = 0.039), with reduction of negative menstrual-related symptoms as the most common reason. Of the athletes reporting regular withdrawal bleedings in connection to HC use, 80% of the progestin-only and 86% of combined HC users experienced negative menstrual-related symptoms, which was comparable to the non-HC group (86%). The majority (81%) of HC users experienced solely positive, or no effect, of HC use on training and performance, with no differences between progestin-only and combined HC users (P = 0.942). Conclusions: In total, 68% of the XC skiers and biathletes used HC, with the highest proportion (64%) using a progestin-only HC. Many athletes used HC to manipulate their menstrual cycle due to perceived negative menstrual-related symptoms that interfered with their training sessions and/or competitions.